Drug repositioning based on centrality measures of drug side effects network / Keng Ying Ying - Keng , Ying Ying (2021)
Drug repositioning, the process of discovering new therapeutic uses of existing drugs, is an alternative to the risky, costly, and time-consuming traditional drug discovery process. Based on the hypothesis that drugs with similar side effects may share similar therapeutic indications, a network of drugs is constructed based on their side-effect similarities. Then, for a target disease of concern, the potential drug candidates that may be repurposed for treating it can be identified from among the network neighbors of the existing drugs approved for the disease. By applying three classic centrality measures – degree, closeness, and betweenness – to rank the drugs in the network, we observe that the drug candidates identified from among the neighbors of the top central drugs approved for our target diseases are more consistent with clinical interests as indicated by the record of clinical trials related to the diseases, when compared to the candidates identified from the neighbors= of their random and peripheral counterparts. The present work indicates that network positions of drugs have a role in repurposing their neighbors and hence should be taken into account in finding new uses of drugs.